Effects of the summer holiday season on UV filter and illicit drug concentrations in the Korean wastewater system and aquatic environment. (August 2017) - Kim, Ki Yong; Ekpeghere, Kalu Ibe; Jeong, Hee-Jin; Oh, Jeong-Eun
Abstract: Seasonal variations in the concentrations of eight ultraviolet (UV) filters and 22 illicit drugs including their metabolites in the Korean aquatic environment were investigated. Seawater samples from three beaches, water samples from two rivers, and influents and effluents from three wastewater treatment plants were analyzed. The UV filter concentrations in the seawater, river water, and effluent samples were 39.4–296, 35.4–117, and 6.84–51.1 ng L -1, respectively. The total UV filter concentrations in the seawater samples were 1.9–4.4 times higher at the peak of the holiday season than outside the peak holiday season. An environmental risk assessment showed that ethylhexyl methoxy cinnamate (EHMC) could cause adverse effects on aquatic organisms in the seawater at the three beaches during the holiday period. Seven of the 22 target illicit drugs including their metabolites were detected in the wastewater influent samples, and the total illicit drug concentrations in the influent samples were 0.08–65.4 ng L -1 . The estimated daily consumption rates for cis -tramadol ( Cis -TRM), methamphetamine (MTP), meperidine (MEP), and codeine (COD) were 25.7–118.4, 13.8–36.1, 1.36–12.6, and 1.75–8.64 mg d -1 (1000 people) −1, respectively. In popular vacation area, the illicit drug consumption rates ( Cis -TRM, MTP and MEP) were 1.6–2.6 times higher at the peak of the summer holiday season than at the beginning of the summer. Graphical abstract: Highlights: Eight ultraviolet (UV) filters and 22 illicit drugs were studied. Total UV filter concentrations in seawater were 1.9–4.4 times higher at the peak of summer vacation. Ethylhexyl methoxy cinnamate (EHMC) could cause adverse effects on aquatic organisms during this period. In holiday areas, illicit drug consumption rates were 1.6–2.6 times higher at the peak of the holiday period. Abstract : The levels of UV filters in seawater, river water and WWTP effluents, and illicit drug including their metabolites in the WWTP influents were assessed to evaluate the summer holiday effect.